2006
DOI: 10.1111/j.1600-0889.2006.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an automatic chamber system for long-term measurements of CO<sub>2</sub> flux from roots

Abstract: A B S T R A C TTo separate CO 2 efflux from roots (R r ) and soil (R s ), we developed a system to measure R r continuously. Using this system, seasonal variation in R r was obtained in a temperate forest in Japan. We measured R s , CO 2 efflux from mineral soil (R m ) and environmental factors simultaneously, and the characteristic and seasonality of R r were analysed in comparison with R s . R r and R s showed different responses to soil water content: R s decreased with decreasing soil water content, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…However, for RR SA and RR VOL (Supplemental Fig. S2), which are rather rarely calculated (Asplund and Curtis, 2001;Desrochers et al, 2002;Dannoura et al, 2006aDannoura et al, , 2006b), significant influences of root diameter were found. RR is dependent on tissue porosity to gas diffusion (Asplund and Curtis, 2001); therefore, it can be anticipated that increasing diameter will increase diffusional limitations in tissues and alter respiration kinetics.…”
Section: Explanatory Value Of Root Diameter Tissue Density and Rootmentioning
confidence: 97%
See 1 more Smart Citation
“…However, for RR SA and RR VOL (Supplemental Fig. S2), which are rather rarely calculated (Asplund and Curtis, 2001;Desrochers et al, 2002;Dannoura et al, 2006aDannoura et al, , 2006b), significant influences of root diameter were found. RR is dependent on tissue porosity to gas diffusion (Asplund and Curtis, 2001); therefore, it can be anticipated that increasing diameter will increase diffusional limitations in tissues and alter respiration kinetics.…”
Section: Explanatory Value Of Root Diameter Tissue Density and Rootmentioning
confidence: 97%
“…Root respiration (RR) accounts for 25% to 60% of total soil respiration (Pregitzer et al, 1997;Epron et al, 1999;Dannoura et al, 2006aDannoura et al, , 2006b) and consumes up to 75% of carbon allocated to roots (Majdi et al, 2007). Predictions on whole-plant carbon budget estimate that total plant respiration is about one-half of gross primary production (Chapin et al, 2012).…”
mentioning
confidence: 99%
“…Soil respiration rates are affected by environmental factors such as soil moisture and soil temperature and by soil properties such as root biomass and porosity (Hanson et al, 2000;Dannoura et al, 2006). Therefore, both environmental factors and soil properties can affect topographic variation in soil respiration.…”
Section: To Amentioning
confidence: 99%
“…The advantage of intact root method is that continuous measurement of respiration could be compared with environmental factors. Respiration rates of intact roots have been measured in the laboratory, by placing plant pots in chambers (Dannoura et al 2005;Edwards 1991), as well as in the field (Dannoura et al 2006a;Chen et al 2009). …”
Section: The Intact Root Methodsmentioning
confidence: 99%